2013
DOI: 10.1016/j.jagp.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Major Carboxyl Terminal Fragments Generated by γ-Secretase Processing of the Alzheimer Amyloid Precursor Are 50 and 51 Amino Acids Long

Abstract: Objectives To understand the cleavage of the amyloid β protein (Aβ) precursor by γ-secretase and determine its changes in a representative Familial (FAD) Alzheimer’s disease (AD) mutation. Methods Transfected cells expressing wild type and FAD mutant APP were analyzed for changes in the levels of the major secreted Aβ species and of the corresponding intracellular C-terminal APP fragments (APP intracellular domain, AICD) generated by γ-secretase whereas radiosequencing was used to precisely identify the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The γ-secretase activity in living cells was calculated by subtracting the unspecific turnover determined by adding 2 μM of the highly specific γ-secretase inhibitor X (Shearman et al, 2000 ). It should be mentioned that similar results showing a decreased γ-secretase activity for several PS1 FAD mutations were observed by us and others in previous studies confirming our assay and the obtained data (Walker et al, 2005 ; Wiley et al, 2005 ; Bentahir et al, 2006 ; Pinnix et al, 2013 ; Grimm et al, 2014 ).…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…The γ-secretase activity in living cells was calculated by subtracting the unspecific turnover determined by adding 2 μM of the highly specific γ-secretase inhibitor X (Shearman et al, 2000 ). It should be mentioned that similar results showing a decreased γ-secretase activity for several PS1 FAD mutations were observed by us and others in previous studies confirming our assay and the obtained data (Walker et al, 2005 ; Wiley et al, 2005 ; Bentahir et al, 2006 ; Pinnix et al, 2013 ; Grimm et al, 2014 ).…”
Section: Methodssupporting
confidence: 92%
“…In contrast to the APPswe mutation affecting β-secretase cleavage, mutations in the catalytically active presenilins affect γ-secretase processing of APP, mainly by shifting the Aβ42/40 ratio towards the generation of the more hydrophobic Aβ42 species (Duff et al, 1996 ; Citron et al, 1997 ; Duering et al, 2005 ). However, several studies have revealed that some of the known PS mutations also reduce γ-secretase processing of APP resulting in decreased AICD levels compared to cells expressing wt presenilins (Walker et al, 2005 ; Wiley et al, 2005 ; Bentahir et al, 2006 ; Pinnix et al, 2013 ). As a genetic approach we analyzed PS-deficient MEFs retransfected with the FAD PS1 mutation T354I (MEF PS1-T354I) compared to PS1 wt (MEF PS1rescue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We would note that previous studies on M139V have led to different conclusions; a cell-free assay had shown that M139V does not alter ⑀-cleavage efficiency but does impair the fourth stepwise cleavage along both product lines when C99 was used as an in vitro substrate (36). In a separate report using a cell model, M139V increased A␤42 but also reduced ⑀-cleavage efficiency (54). However, our present results are consistent with a previous study from our group where we found that the M139V mutant selectively raised A␤42 but did not alter levels of other peptides in CHO cells stably overexpressing this mutant (55).…”
Section: Discussionmentioning
confidence: 82%
“…13B). Arc's activation of the γ-secretase PSEN1 to promote cleavage of APP not only increases amyloid beta load, but also results in an increased level of the APP intracellular domain (AICD) 80,176 . AICD forms a complex with TIP60/Kat5 to alter transcriptional activity crucial for AD progression 150,[177][178][179][180][181][182] (Fig.…”
Section: Gsk3b Although Glycogen Synthase Kinase 3 Beta (Gsk3b)mentioning
confidence: 99%